Accuracy in determining serum glucose, cholesterol and triglycerides levels in clinical laboratories of Lima, Peru - Sandoval Vegas, Miguel H. (2012)
Objectives: To assess the accuracy of clinical laboratories in Lima in the determination of glucose, cholesterol and triglycerides. Design: Descriptive. Location: Center for Research in Biochemistry and Nutrition, Faculty of Medicine, San Marcos University, and clinical laboratories participating in Lima. Materials: Serum samples from donors. Interventions: Prior informed consent, serum samples were sent in 4-6°C cold chain to 88 blind duplicate clinical laboratories sampled. Results were received via email and arithmetic mean, standard deviation (SD), coefficient of variation (CV) and standard deviation index (SDI) were obtained; accuracy was assessed using the validation of biological variability (BV). Main outcome measures: Glucose, cholesterol and triglycerides levels. Results: The majority (>75%) of laboratory results were within acceptable range; laboratories out of control range were 9,1 to 12,5%. Quality index by biological variability for most laboratories was in control, whether optimal, desirable or minimum; 42% of the laboratories were found out of control for cholesterol testing, 25% for glucose, and 11.4% for triglycerides. Laboratories with automated equipment had better accuracy. Conclusions: Most clinical laboratories had good measurements accuracy; however, there were several laboratories with extensive vagueness in their results where efforts should be done to improve these quality indices.